Design and Construction of Electrical Magnate to Study its Efficiency and the Optimum Parameters to Produce Alkaline Magnetic Water and Treating the Sea Water to be Suitable for Irrigation - Al-Bayati, Alaa Dhari Jawad (Al-Khwarizmi Engineering Journal, 2015)
AbstractElectrical magnate  was designed and constructed,  the optimum Magnetic flux  and the effect of time on the physical properties of the alkaline (magnetic water) produced from the bottled drinking water [the total dissolved solids (TDS) or the electrical conductivity, and pH] were studied, to simulate ZamZam water in Mekka Saudi Arabia. Also, the efficiency of magnetic field from this designed electrical magnate in decreasing the TDS of sea water (of 1500 ppm NaCl Content), to convert it to water suitable for irrigation (TDS